The impact of alcohol consumption on nutritional status (Research, Society and Development, 2023)
Alcohol is the fermentation of carbohydrates present in vegetables such as sugar cane, grapes and barley. Regarding the composition, it has the minimum amounts of nutrients and minerals. In addition to having 7 kcal/g. The objective of this study was to evaluate the effects of alcohol on the nutritional status of individuals, discussing the harmful effects of consuming this substance on health. It was a literature review, based on scientific articles and books in Portuguese and English, published from 2002 to 2022. The searches were carried out in the Scielo, Pubmed and Google Scholar databases. In view of the analyzed studies, alcohol abuse is more frequent in socially excluded individuals and with unstable living conditions. Nutritional status is assessed using the Lean Mass Index (BMI), Triceps Skinfold (TCP), Arm Muscle Circumference (AMC) and Bioelectrical Impedance (BIA) parameters, Ultrasonography, Magnetic Resonance Imaging (MR) and Computed Tomography (TC). In view of the results found, cases of malnutrition and excess weight were observed, in addition to other pathologies related to chronic alcohol abuse, such as nutrient deficiencies, malnutrition, liver diseases, alcoholic hepatitis and cirrhosis. Given the above, it is important to emphasize the importance of follow-up by a professional nutritionist for an adequate nutritional status.